2016
DOI: 10.1007/s11356-016-7512-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of PBDEs and PAHs in house dust in Kocaeli, Turkey: levels and sources

Abstract: Indoor dust samples were collected from 40 homes in Kocaeli, Turkey and were analyzed simultaneously for 14 polybrominated diphenyl ethers (PBDEs) and 16 poly aromatic hydrocarbons (PAHs) isomers. The total concentrations of PBDEs (ΣPBDEs) ranged from 29.32 to 4790 ng g, with a median of 316.1 ng g, while the total indoor dust concentrations of 16 PAHs (ΣPAHs) extending over three to four orders of magnitude ranged from 85.91 to 40,359 ng g with a median value of 2489 ng g. Although deca-PBDE products (BDE-209… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 83 publications
2
15
1
1
Order By: Relevance
“…The same pattern of exposure risks are revealed for metal exposure: Dermal contact, followed by ingestion, while exposure via inhalation is negligble (dermal contact > ingestion > inhalation). This finding is consistent with a similar study on e -waste sites reported by Civan and Kara 2016 [56] and review studies by Song et al, 2015 [57]. The health risk for the metals were much more pronouced than those for PBDEs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The same pattern of exposure risks are revealed for metal exposure: Dermal contact, followed by ingestion, while exposure via inhalation is negligble (dermal contact > ingestion > inhalation). This finding is consistent with a similar study on e -waste sites reported by Civan and Kara 2016 [56] and review studies by Song et al, 2015 [57]. The health risk for the metals were much more pronouced than those for PBDEs.…”
Section: Discussionsupporting
confidence: 91%
“…It is crucial that e -waste workers are educated on the potential health risks peculiar to their jobs and the safety measures to be undertaken. It is also important to note that non- e -waste workers, residents, and children around the e -waste sites are very likely to also be at risk of adverse health effects from informal e -waste recycling as also pointed out by References [15,56,57,60]. The other informal non- e -waste workers around the e -waste recycling vicinity have similar socio-demographics and work conditions [61], hence they are likely to be exposed to similar health risks like the e -waste workers.…”
Section: Discussionmentioning
confidence: 99%
“…Nồng độ PAHs trong mẫu bụi trong nhà ở Hà Nội thấp hơn đáng kể so với một số khu vực ở Trung Quốc với nguồn phát thải đặc thù như khu dân cư gần đường vận chuyển dầu diesel ở Nantou, Đài Loan (trung vị 107.400, khoảng 16.000-580.000 ng/g) [25] hay các nhà dân sử dụng than đá làm nhiên liệu đốt chủ đạo ở Qingyang, tây bắc Trung Quốc (trung vị 21.000, khoảng 8450-121.000 ng/g) [26]. Hàm lượng PAHs trong các mẫu bụi trong nhà của nghiên cứu này phù hợp với khoảng nồng độ đo được trong mẫu bụi tại các nước đang phát triển khác như Saudi Arabia và Kuwait [27], Thổ Nhĩ Kỳ [28], Jordan [29] và Nepal [30]. Như vậy, mức độ ô nhiễm PAHs trong mẫu bụi trong nhà và ngoài đường ở Hà Nội nằm trong khoảng trung bình hoặc thấp so với các quốc gia khác trên thế giới.…”
Section: Nồng độ Pahs Trong Mẫu Bụiunclassified
“…In particular the PAH in particulate data is used to calculate incremental lifetime cancer risk for the exposed population [104, 107, 119, 125, 126, 140, 141, 149, 150, 157, 160, 161, 176, 190-192, 214, 221, 222, 228-231]. Three pathways for exposure from PAH in particulates are discussed: i) Ingestion [104,141,149,150,176,190,214,220,222,223,[231][232][233][234][235]; ii) Dermal contact [104,141,149,150,176,214,220,222,223,231,233,235]; and iii) Inhalation exposure [105,131,137,141,142,147,152,159,160,177,181,191,193,208,210,213,220,221,…”
Section: Pah Source Apportionmentmentioning
confidence: 99%